Use of covered self-expandable stents for benign colorectal disorders in children - Lange, Bettina; Sold, Moritz; Kähler, Georg; Wessel, Lucas; Kubiak, Rainer (Journal of pediatric surgery, 2017)
Purpose: There is a lack of experience with covered self-expandable stents for benign colorectal disorders in children. Methods: Five children (4M, 1F) with a median age of 5years (range, 6months-9years) who underwent treatment with covered self-expandable plastic (SEPSs) or self-expandable metal stents (SEMSs) for a benign colorectal condition between April 2005 and November 2013 were recruited to this retrospective study. Etiologies included: anastomotic stricture with (n=1) or without (n=3) simultaneous enterocutaneous fistula, as well as an anastomotic leak associated with enterocutaneous fistula (n=1). All children suffered from either Hirschsprung's disease (n=3) or total colonic aganglionosis (Zuelzer-Wilson syndrome) (n=2). Results: Median duration of individual stent placement was 23days (range, 1-87days). In all cases up to five different stents were placed over time. At follow-up two patients were successfully treated without further intervention. In another patient the anastomotic stricture resolved fully, but a coexisting enterocutaneous fistula persisted. Overall, three patients did not improve completely following stenting and required definite surgery. Stent-related problems were noted in all cases. There was one perforation of the colon at stent insertion. Further complications consisted of stent dislocation (n=4), obstruction (n=1), formation of granulation tissue (n=1), ulceration (n=1) and discomfort (n=3). Conclusions: Covered self-expandable stents enrich the armamentarium of interventions for benign colorectal disorders in children including anastomotic strictures and intestinal leaks. A stent can be applied either as an emergency procedure (bridge to surgery) or as an adjuvant treatment further to endoscopy and dilatation. Postinterventional problems are frequent but there is a potential for temporary or definite improvement following stent insertion.
Available online 6 February 2016
Gesehen am 15.10.2018